The use of cassava leaf silage as a feed supplemental in diets for ruminants and its introduction to smallholder farmers - Marjuki, HE; Sulistyo, DW; Rini, I; Artharini, I; Soebarinoto; Howeler, Reinhardt H. (2008)
Introduction of cassava leaf silage making to smallholder farmers and its feeding to ruminants in cassava crop growing areas were investigated through laboratory and on-farm feeding trials, extension services and training. This with the aim to evaluate the response of the ruminants on cassava leaf silage feeding and the adoption of the technology by farmers.